رحيق التفاسير للمائدة، التوبة، الإسراء، مريم، وطه من سور القرآن الكريم (Rahiq al-tafasir lil-Ma'idah, al-Tawbah, al-Isra', Maryam, wa Taha min suwar al-Qur'an al-karim) - Al-Khairabadi, Prof. Dr. Mohammed Abullais (IIUM Research Center, 2003)
Rahique Attafasir for Chapters 5, 17, 19, and 20 of The Holy Quran